Mozzarella Cheese Processing Training for Farmers in Tonjong Village, Tajurhalang District, Bogor Regency - Rismaya, Rina; Noviyanti, Rinda; Ulfah, Mutiara; Nadia, Lula; Maulida, Iffana Dani; Wicaksana, Bayu Eka; Susilo, Adhi (JAKADIMAS (Jurnal Karya Pengabdian Masyarakat), 2024)
One of the main problems faced by farmers in Tonjong Village, Tajur Halang Regency, Bogor is that the selling price of pure milk in 1 liter is quite low. Public knowledge regarding processing technology to increase product added value is still low, which is the reason farmers sell pure milk directly. This community service training aims to determine the effect of processing pure milk into mozzarella cheese on increasing community knowledge and skills. This increase in knowledge was measured using a one group pretest posttest design which was carried out in a prametric analysis using a paired sample t-test to see the difference in the mean scores. This training activity was given to 10 people in the community around the cattle farm in Tonjong Village who had an age range of 26-70 years and had the last education from elementary to high school. The results of this training community service indicate that there is a significant effect of giving on increasing community knowledge as evidenced by the significantly different pretest (68%) and posttest (87%) values (p <0.05). The expected results of community service can be implemented independently by breeders to increase the added value of dairy products through the processing of mozzarella cheese.